2021
DOI: 10.1111/aogs.14080
|View full text |Cite
|
Sign up to set email alerts
|

Barbed vs conventional suture at cesarean delivery: A systematic review and meta‐analysis

Abstract: Introduction: Barbed sutures are used in cesarean delivery with the intended benefits of better tissue approximation, hemostasis, and strength, as well as reduced operative time. A systematic review and meta-analysis was undertaken to assess the safety and efficacy of the use of barbed suture compared with conventional sutures in cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…They can reduce the wound closing time and improve the operation efficiency. Recently, Agarwal et al [ 5 ] In comparison with the use of barbed suture and absorbable sutures in cesarean delivery, it is shown that the barbed suture can replace the absorbable common suture, which can reduce the time of closure and incidence rate of wound complications. However, these studies only focused on the comparison between barbed suture and ordinary suture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They can reduce the wound closing time and improve the operation efficiency. Recently, Agarwal et al [ 5 ] In comparison with the use of barbed suture and absorbable sutures in cesarean delivery, it is shown that the barbed suture can replace the absorbable common suture, which can reduce the time of closure and incidence rate of wound complications. However, these studies only focused on the comparison between barbed suture and ordinary suture.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NMA combines many published RCTs, which have a broader basis, comprehensively evaluate several types of skin closure materials, and integrate direct and indirect comparisons. And from the cost effect analysis, the cost of barbed suture is much higher than that of ordinary suture [ 5 ]. This study has clinical significance because it qualitatively compares the selection of appropriate skin closure materials to close the wound during cesarean delivery and provides a reference for obstetricians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last 10 years, barbed sutures have been proposed to close the hysterotomy during CD. A systematic review with meta‐analysis showed that the use of a barbed suture during CD may lead to significant advantages in terms of reduced surgical time and need for additional hemostatic sutures, without increasing morbidity or estimated intraoperative blood loss compared with conventional smooth (monofilament/multifilament) suture 10 . Because a barbed suture provides constant tension on tissue, which improves bleeding control, 9 its use may lead to improved uterine wall healing following CD, therefore also reducing the formation of uterine scar defects (considered a surrogate endpoint for future uterine rupture and abnormal placentation) 4,5 .…”
Section: Introductionmentioning
confidence: 99%